Students in the light of studies of self-perceived employability and information management skills - Świgoń, Marzena (Qualitative and Quantitative Methods in Libraries; Vol 11 No 1 (2022): March issue 2022, 2022)
Abstract:   The problem of self-perceived employability, the concept connected with personal knowledge and information management in the context of students was described. The self-perceived employability can be defined as the ability to keep the job and as the ability to get the job one desires. And highly educated young people in variety of European Union countries, including Poland, are often unsatisfied with his or her first job. The empirical studies were conducted among the Polish and German students of various majors. A special scale was used which consisted of 19 statements regarding five components: 1) student’s perception of university, 2) field of study, 3) self-belief, 4) state of the external labour market and 5) personal knowledge and information management. The last component, that is the PKIM-personal knowledge and information management, is strongly connected to information literacy, well known in the library and information science literature. The findings of these studies were compiled using statistical methods: descriptive and inferential statistics and compared with the findings of other studies in this scope. Limitations were discussed as well as the implications for the future research of this problematic.